CRITICISM ABU RAYYAH TO ABU HURAIRAH - Arifin, Syamsul (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2016)
Hadith is a collection of information about all the words, deeds and decrees of the Prophet. While the Sunnah is a concept of behavior, which is based either on the deed or only the approval of the Prophet. What is written in the hadith is not all that the Sunnah can say. But the Sunnah is also not all recorded in the Hadith. In its journey, the internal political conflict of the Muslim Ummah has for some time caused the Hadith to undergo much distortion even further falsified forgery. Since the 14th century H until now often mentioned as the era of revival of the second Hadith study after stagnant around the 10th - 14th century H. In addition to reaping positive responses It is also widely responded negatively by some who consider this movement as the Flow Inkar-Sunnah Modern. This reform movement was first launched by Muhammad Abduh (1266-132 H / 1849-1905 AD). In its development many of the figures of thought in the study of contemporary hadith that emerged after the time of Muhammad Abduh, among them is Mahmud Abu Rayyah, whose thoughts are heavily influenced and refers to the opinions of Muhammad Abduh and Muhammad Rashid Rida. In this paper will be written some data that have been collected about Mahmud Abu Rayyah and his work is quite controversial.